KADARsIgA DAN LACTOFERRINAIR SUSU IBU - Permaesih, Dewi; ., Hardinsyah; Setiawan, Budi; Tanumihardjo, Sherry A (PERSATUAN AHLI GIZI INDONESIA, 2009)
sIgALACTOFERRIN LEVEL IN BREAST MILKBreast milk offers innumerable immunological components that are important for reduction of infantmorbidity and mortality. Breast milk protects against infections in breastfed newborns mainly viasecretory IgA (sIgA) antibodies, but also most likely via several other factors such as the bactericidallactoferrin. The purpose of this article is to determine the levels of sIgA and lactoferrin of breast milkfrom Indonesian women in Pandeglang. sIgA and lactoferrin in breast milk were measured crosssectionally in postpartum women between lactation days 14 -28 using ELISA. Results showed thatthe mean level of sIgA from 137 breast milk samples was 2.11 ± 3.5 mg/ml and that of lactoferrin from138 samples was 3.73±4.05 mg/ml. The mean levels of sIgA and lactoferrin in this group are lowerwhen compared with other published values.Keywords: breast milk, secretory IgA (sIgA), lactoferrin